Analisis Hasil Pemeriksaan Viral Load Dan CD4 Pada Penderita HIV Di RSUD Pandan Arang Boyolali Periode Tahun 2022 - Wirna Sari; Farida Noor Irfani (Lembaga Pengembangan Kinerja Dosen, 2024)
Acquired Immunodeficiency Syndrome disease cause HIV. This disease damages the body's immune system known as CD4. CD4 lymphocyte count is associated with disease progression, increased opportunism, and mortality. Laboratory examination required to determine the CD4 count using this method flowcytometry, and test viralload PCR method. The of research is analyze results of viralload and CD4 in HIV sufferers at RSUD Boyolali . Quantitative research method with analytical descriptive design. Data univariate and bivariate with the chi-square test to see the magnitude of relationship between the independent variables and HIV infection. total of 94 patients in 2022 showed several normal and abnormal results, where values ​​were normal viralload <10,000copy/ml low, >100,000copy/ml high, and <40copy/ml not detected. Normal CD4 results 410 – 1,600 cells/ml and low <500 cells/ml. CD4 research results and viralload normal 43 (46%) patients, CD4 results and viralload abnormal in about 9 (9%), and 1% of patients with normal CD4 countsviral load abnormal patient has not received treatment. CD4 examination uses the method flowcytometry whereas viral load using the PCR method and blood plasma samples. There is relationship viralload method PCR dan CD4 method flowcytrometry with significance value of 0.013. Further research needs to be carried out using experimental methods.